Implementasi Nilai-Nilai Keislaman melalui Mata Pelajaran Al-Islam dan Kemuhammadiyahan di MA Muhammadiyah Bandung - Tulungagung - Ananda Nikmatul Oktaviani; Suripto Suripto (Departement of Mathematics Education, 2024)
This research is motivated by social, religious and moral anxiety caused by a lack of understanding of the boundaries between good and bad, so there is a need for reform in the field of education. Education as an institution strives to implement the values ​​contained in Muhammadiyah subjects. These values ​​include upholding the pure creed of monotheism, morals, ammar ma'ruf nahi munkar, worship and muamalah, as well as renewal in the understanding and practice of Islamic teachings towards purity in accordance with the Al-Qur'an and Sunnah, so that a truly Islamic society can be realized. This research uses a qualitative approach with data collection techniques, namely observation, interviews and documentation. The conclusion of the research is that the implementation of Muhammadiyah values, namely the values ​​of aqidah, worship, morals and muamalah, is through understanding Muhammadiyah education, example, habituation of morals and worship, advice and Muhammadiyah organizations at MA Muhammadiyah Bandung Tulungagung.